1976
DOI: 10.3168/jds.s0022-0302(76)84267-1
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Plasma Corticoids During Parturition

Abstract: Concentrations of adrenal corticoids in plasma were determined by a competitive protein-binding technique using jugular blood samples taken three times daily and more frequently during labor from 21 cows before and after parturition. The prepartum value was 6 ng/ml with a sharp rise during the last 16 h before calving. The average value at the time of calving was 19.2 ng/ml with a significant drop 1 h after calving to 11.2 ng/ml and a return to basal concentrations by 3 days postpartum. Evidence that labor is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 16 publications
6
34
0
1
Order By: Relevance
“…Plasma concentrations of cortisol are usually increased at parturition (Smith et al, 1973;Hudson et al, 1976). An increase in concentrations of cortisol in plasma of cows at parturition was probably not detected in the present experiments because cows were only sampled once a day or stress of sampling influenced secretion of cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma concentrations of cortisol are usually increased at parturition (Smith et al, 1973;Hudson et al, 1976). An increase in concentrations of cortisol in plasma of cows at parturition was probably not detected in the present experiments because cows were only sampled once a day or stress of sampling influenced secretion of cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the concentrations of plasma cortisol were markedly high at 24 h before parturition and peaked at the time of parturition ( Smith et al . 1973 ; Hudson et al . 1974 ; Hunter et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an effect of parity on hair cortisol concentration was observed only in samples collected before parturition (L0), and not in those from the lactation period. Since the HPA axis has a crucial role in initiating parturition, the plasma cortisol concentration peaks at parturition and returns to the basal concentration by 3 days postpartum (Hudson, Mullford, Whittlestone, & Payne, 1976). Since the HPA axis has a crucial role in initiating parturition, the plasma cortisol concentration peaks at parturition and returns to the basal concentration by 3 days postpartum (Hudson, Mullford, Whittlestone, & Payne, 1976).…”
Section: Discussionmentioning
confidence: 99%